A Mother’s Refrain: Judges 5:28-30 in Cultural Context - Baker, Robin ca. 20./21. Jh. (Vetus Testamentum, 2017)
The Song of Deborah’s unusual language and style, and the potency of its imagery combine to make it one of the most analysed and debated texts in the Hebrew Bible. Although many aspects of the Song have remained opaque, there is scholarly consensus that it was composed in approximately the form we have it in the period of the Judges. This consensus is largely founded on linguistic analysis of the text. This article approaches the Song from a different direction. It considers the cultural markers found in Judges 5:28-30 and analyses what they reveal about the Sitz im Leben of these verses.